PERSEPSI AKUNTAN PUBLIK DAN AKUNTAN PENDIDIK TERHADAP KONSEP DASAR, PENGUKURAN DAN PENGUNGKAPAN AKUNTANSI LINGKUNGAN - Mela Febri Yanti; Ethika Ethika; Ari Frinola Minovia (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2021)
This study aims to examine empirically the differences in auditors and lecturers' perceptions of basic concepts, measurements and environmental accounting disclosures.This research was conducted at Public Accountants registered at the Indonesian Institute of Public Accountants (IAPI) in Padang City and Accounting Educators who hold accountants at State and Private Universities in Padang City. The sample selection was based on convenience sampling method and finally obtained 31 auditors and 31 lecturers who had met the criteria for sampling. The data analysis technique used to test the hypothesis is the Independent Sample t-Test using SPSS version 16 software. The results of this study indicate that there are differences in perceptions between public accountants and educating accountants on the basic concepts of accounting, But according to public accountants and educating accountants, there are no differences in the measurement of environmental accounting and environmental accounting disclosures.